‘EXCELSIOR’ H2020 Widespread Teaming Phase 2 Project: Earth Observation and Geoinformatics Research and Innovation Agenda for Cultural Heritage - Hadjimitsis, Diofantos G.; Leventis, Georgios; Cerra, Daniele; Themistocleous, Kyriacos; Kyriakidis, Phaedon; Agapiou, Athos; Makri, Despina; Papageorgiou, Nikoletta; Danezis, Chris; Lysandrou, Vasiliki; Tzouvaras, Marios; Mettas, Christodoulos; et al. (My University, 2020)
This paper presents how the EXSELSIOR H2020 Teaming project will support the management and monitoring of the cultural heritage domain through its research and innovation agenda within the Eastern Mediterranean, Middle East, and North Africa (region known as EMMENA). The pressing need for protecting the cultural heritage assets is highlighted throughout the document by reviewing the conducted research work in key funded projects attained in the past by the Cyprus University of Technology team in collaboration with EXCELSIOR’s partners.
Keywords: EXCELSIOR; Geoinformatics; Earth observation; Cultural heritage